Sustainability indicators of the Brazil nut tree management - Fernanda Lopes da Fonseca; Oscar José Rover; Lucia Helena de Oliveira Wadt; Cleisa Brasil da Cunha Cartaxo (Revista Brasileira de Ciências Ambientais, 2021)
Brazil nut tree (Bertholletia excelsa Bonpl) management, is a traditional activity that plays a key role in the economy of forestbased Amazon communities and in the conservation of forests. Nevertheless, some threats and critical points related to sustainability indicate to the need for establishment of monitoring procedures that can assist in the management of this natural resource. The overall aim of the research was to evaluate the MESMIS method as a tool to support the participatory definition of sustainability indicators to monitor Brazil nut management, and the viability of Brazil nut harvest over time. For that, we carried out a case study in the Porvir Community, RESEX Chico Mendes, Acre State (Brazil), aiming to integrate the perceptions of Brazil nut harvesters, researchers, managers, and technicians to define the indicators. The result was the generation of 18 strategic indicators to assess sustainability in the environmental, technical-economic and social dimensions. Assessment parameters, representing conditions that must be achieved for system sustainability, were collectively defined for each indicator. The main critical values attributed in the evaluation of the indicators are related to Brazil nut commercialization to intermediaries and oscillation in the annual fruit production. The use of the MESMIS method was considered appropriate to the studied context and can be recommended to similar non-timber forest product management systems.